2012
DOI: 10.1016/j.jvs.2012.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Quality of vascular surgery Web sites on the Internet

Abstract: Internet information on vascular surgical conditions and procedures is poorly written and unreliable. We suggest that health professionals should recommend Web sites that are easy to read and contain high-quality surgical information. Medical information on the Internet must be readable, accessible, usable, and reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…DISCERN is a validated instrument designed to assess the quality of written information on treatment choices, and can be applied to any disease ( Supplementary Appendix Table E1). 3 Sixteen questions are rated from 1 (low quality/not addressed) through 5 (high quality/fully addressed). Questions 1-8 evaluate publication reliability, questions 9-15 evaluate the quality of information regarding treatment options, and question 16 evaluates the overall publication.…”
Section: Discern Scoringmentioning
confidence: 99%
See 1 more Smart Citation
“…DISCERN is a validated instrument designed to assess the quality of written information on treatment choices, and can be applied to any disease ( Supplementary Appendix Table E1). 3 Sixteen questions are rated from 1 (low quality/not addressed) through 5 (high quality/fully addressed). Questions 1-8 evaluate publication reliability, questions 9-15 evaluate the quality of information regarding treatment options, and question 16 evaluates the overall publication.…”
Section: Discern Scoringmentioning
confidence: 99%
“…Despite these advantages, there are concerns regarding the accuracy and reliability of online health information, and there is significant potential for patients to be misinformed. 3,4 In addition, many online resources are written at a high reading level, which negatively impacts patient understanding, compliance, and overall health. 5 Idiopathic pulmonary fibrosis (IPF) is a chronic, fibrosing interstitial pneumonia of unknown etiology that is characterized by progressive dyspnea, worsening lung function, and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the score is, the easier the readability of a piece of text. Scores of 60-70 should be understandable by those aged 13-15 years old (Grewal et al, 2012). The remaining three tests all output a corresponding US school grade level, a breakdown of which can be found in Table 3, along with reflective age numbers.…”
Section: The Readability Testsmentioning
confidence: 99%
“…However in studies using LIDA and the Flesch Reading Ease score, an observed correlation between the two was seen. [20][21][22] Readability ease is calculated using a mathematical formula considering average sentence length and average number of syllables per word. 23 Inter-observer variation in scoring was minimized by having a single researcher perform all website assessments.…”
Section: Being Balanced and Unbiasedmentioning
confidence: 99%
“…Finally, while urologists may not represent all types of doctors in cyberspace, a trend in the literature, across multiple specialties has called for an improvement in the quality of medical websites. [20][21][22]25 …”
Section: Being Balanced and Unbiasedmentioning
confidence: 99%